Taxation of the Agricultural Sector in the System of Ukraine’s Economic Policy Implementation and its Digitalization - Nesenenko, Pavlo (Dr. Viktor Koval, 2022)
Introduction. The agricultural sector is a strategically important segment for ensuring the country's national security. New challenges rightly require appropriate responses. All means of regulating the state agrarian sector, first of all, should be aimed at ensuring its successful development and effective functioning. The development of the agrarian sector of Ukraine requires the solution of institutional problems of agrarian production Studying literary sources indicates that state economic policy is implemented, primarily, through the mechanisms of tax policy, which has notes permanent changes in recent years. Aim and tasks. The aim of this article is to research the taxation of the agricultural sector in the system of Ukraine’s economic policy implementation and its digitalization. A secondary aim would be to single out the advantages and disadvantages of the taxation system and to create recommendations on choosing a taxation system for subjects of the agrarian sector. Results. The taxation of the agricultural sector in the system of Ukraine’s economic policy implementation and its digitalization are researched. Such stages of legal regulation of agricultural protection tax relations as formation (establishment), relative permanence, reformation, and post-reformation (post-reform stage) are defined. The agricultural protection tax measures in terms of VAT taxation during the period are performed. The advantages and disadvantages of the taxation systems of agricultural sector entities are singled out. Recommendations on choosing a taxation system for subjects in the agrarian sector are formed. The structure of the "Manager" module in the program "BAS AGRO. Accounting" is shown. Conclusions. Each of the tax systems that can be used by subjects of the agrarian sector has its own advantages and disadvantages. It is necessary to take into account the conditions under which a specific enterprise operates. The performed analysis of the evolution of the tax legislation in terms of taxation of the agrarian sector indicates a reduction in agro-protective actions by the state. At the stages of formation (establishment) and relative permanence of legal regulation, the introduction and effective use of tax policy, in particular the fixed agricultural tax and the special VAT taxation regime, were observed. During the reform and post-reform stages, the agricultural protection measures outlined above, which were quite powerful and effective at the time, were significantly minimized. The actual adaptation of information technologies to the needs of agriculture is one of the best new technologies in the agricultural sector.